2019
DOI: 10.1186/s40068-018-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of ceramic filters for water treatment in Kambata Tabaro zone, southern Ethiopia

Abstract: Background: The Ceramic water filtration has been greatly improving the most waste materials from drinking water in developing countries. This research was carried out to determine the efficiency of the Ceramic water filters in improving water impurities. The raw materials were grind, sieved with 0.5 mm opening mush size, mixed with water, molded in flower pot shape and fired at 700 °C, 750 °C and 800 °C. Results: The average removing efficiency of the ceramic filters was found to be 59.6%, 86.3%, 87.6%, 56.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 9 publications
6
23
0
Order By: Relevance
“…In fact, the particles tend to agglomerate with each other with increasing temperature leading to a more consolidated ceramic body. These results are similar to those of [4].…”
Section: Influence Of Sintering Temperature On Water Of Absorption Casupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, the particles tend to agglomerate with each other with increasing temperature leading to a more consolidated ceramic body. These results are similar to those of [4].…”
Section: Influence Of Sintering Temperature On Water Of Absorption Casupporting
confidence: 90%
“…These properties are linked to the amount of porogen and sintering temperature. Previous works in the field have shown that porosity of ceramic filters decreases with increase in firing temperature for the same composition of clay and porogen fired at different temperatures [4] and that the physico-chemical stability increases with increase in firing temperature due to the formation of more crystalline phase such as mullite [5]. But no matter the crystalline phase present in the material it's stability can be influenced by the physico-chemical properties of the feed water such as pH.…”
Section: Introductionmentioning
confidence: 99%
“…It was clear from Figure 6, the average flow rate for Kaolin-jute fibers filters were: 1.57 L/h, 1.95 L/h, and 2.43 L/h for filter 1, filter 2, and filter 3, respectively. Which was within the acceptable limits of flow rates (1-2) L/hr, according to Brown [22] studies. Filters can produce sufficient cooking and drinking water for a household of small members due to their flow rates.…”
Section: Figure 6 Average Flow Rate For Kaolin-jute Fibers Filterssupporting
confidence: 64%
“…The raw water samples used in this study were taken from Shatt Al Hilla river at Al-Hilla city/Iraq Samples of water with different turbidities (5,15,30,50, and 80) NTU were taken. Figures 3, 4 and 5 show a map of Hilla River, a general location and exact location of the study area respectively.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation